The Development of Ethnotourism in the Carpathian Region - Shykerynets, Vasyliy; Gumenyuk, Andrew (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article deals with the nature, theoretical and methodological framework and resource base of ethnotourism in the Carpathian region. It examined the concept and components of ethnic tourism resources & analyzed their provision in the Carpathian region. Also the problem of development of ethnotourism was identified in this region.